Characteristics of agricultural soils and the reality of their investment in eastern Maysan governorate using geograpHic information systems (GIS) - General Directorate of Maysan Education Master of Agricultural GeograpHy ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research aims to study the pHysical and chemical properties of agricultural soils and their role in establishing an economically feasible agricultural investment in the eastern regions of Maysan Governorate, which lies within the international border belt with the Republic of Iran. The results of laboratory analyzes conducted for (36) models of the first two depths (0-30 cm) revealed ) and the second (31-60 cm). It included the pHysical properties (soil texture, porosity, moisture content), chemical properties (pH, electrical conductivity, Ec, total organic carbon, Toc), as well as some nutrients dissolved in the soil solution (nitrogen N, pHospHorous Po4, potassium K), which Together, they contribute to influencing the reality of agricultural investment in the region. And it became clear that there is a diversity in the soils of the region, as it represents the soils of the eastern hills, alluvial fans, the soils of the rivers and their basins, as well as the soils of the marshes and sand dunes. agricultural investment in it.